Development of an LC–MS/MS method for quantification of two isomeric phenylpropenes and the application to pharmacokinetic studies in rats. (27th October 2017) - Yang, Qiong; Deng, Zhipeng; Zhang, Fang; Sun, Peilu; Li, Jun; Zheng, Wanjin
Abstract: Isomers β ‐asarone and α ‐asarone have recently been demonstrated to have differentialpharmacological activities . Here, we report an LC–MS/MS method developed using acetonitrile to extract two isomeric phenylpropenes from rat plasma. Separation was achieved using a XDB‐C18 column (100 × 2.1 mm; i.d., 1.8 μm) with a mobile phase of methanol–0.1% formic acid (55:45, v /v) at a flow rate of 0.3 mL/min. Calibration curves ranging from 5.20 to 2080 ng/mL for β ‐asarone and from 3.68 to 1470 ng/mL for α ‐asarone were linear ( r 2  ≥ 0.9938) with the lower limits of quantification being 5.20 and 3.68 ng/mL for both isomers. Intravenous administration of β ‐asarone (2.22 mg/kg) and α ‐asarone (2.36 mg/kg) in rats yielded half‐lives of 13.40 ± 4.11 and 28.88 ± 7.82 min with clearance values of 0.196 ± 0.062 mL/min/kg and 0.112 ± 0.012 mL/min/kg for β ‐asarone and α ‐asarone, respectively.